Effect of di-calcium phosphate on calcium balance and body condition score of dairy cows fed Napier grass - Rahman, MZ; Ali, MY; Huque, KS; Talukder, MAI (Bangladesh Journal of Animal Science, 2014)
A research work was undertaken to evaluate the feeding effects of di-calcium phosphate (DCP) on calcium balance and body condition score of dairy cows fed Napier grass. The trial was conducted in the village Alokdiar of Shajadpur upazilla under Sirajgonj district. Twenty crossbred lactating dairy cows of 320 ±15.5 kg live weight were used for the trial. Animals were equally and randomly allocated into four groups, T0 (Napier+concentrate), T1 (Napier+concentrate+100g DCP), T2 (Napier+concentrate+150g DCP) and T3 (Napier+concentrate+200g DCP). Total DMI did not differ significantly (p>0.05) among the groups but highly significant differences (p<0.01) were found in Ca intake. Ca balance; and Ca in feces, Ca in urine, Ca in milk and total Ca excretion differed significantly (p<0.05). No significant difference (p>0.05) was found in DM in feces (%), DM in feces (kg/d) and milk production (L) among the treatment groups except urine excretion. There was a linear increase of body condition score (BCS) with DCP (T1, T2 and T3), but BCS was linearly declined in non DCP diet (T0). Diets with 150g DCP may be suggested for optimizing Calcium balance and body condition score of dairy cows fed Napier grasses. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21648 Bang. J. Anim. Sci. 2014. 43 (3): 197-201